Phosphorylation of Transcription Factor Specificity Protein 4 Is Increased in Peripheral Blood Mononuclear Cells of First-Episode Psychosis - Pinacho, Raquel; Saia, Gregory; Fusté, Montserrat; Meléndez-Pérez, Iria; Villalta-Gil, Victoria; Haro, Josep Maria; Gill, Grace; Ramos, Belén (PLOS ONE, 2015)
Background Altered expression of transcription factor specificity protein 4 (SP4) has been found in the postmortem brain of patients with psychiatric disorders including schizophrenia and bipolar disorder. Reduced levels of SP4 protein have recently been reported in peripheral blood mononuclear cells in first-episode psychosis. Also, SP4 levels are modulated by lithium treatment in cultured neurons. Phosphorylation of SP4 at S770 is increased in the cerebellum of bipolar disorder subjects and upon inhibition of NMDA receptor signaling in cultured neurons. The aim of this study was to investigate whether SP4 S770 phosphorylation is increased in lymphocytes of first-episode psychosis patients and the effect of lithium treatment on this phosphorylation. Methods A cross-sectional study of S770 phosphorylation relative to total SP4 immunoreactivity using specific antibodies in peripheral blood mononuclear cells in first-episode psychosis patients (n = 14, treated with lithium or not) and matched healthy controls (n = 14) by immunoblot was designed. We also determined the effects of the prescribed drugs lithium, olanzapine or valproic acid on SP4 phosphorylation in rat primary cultured cerebellar granule neurons. Results We found that SP4 S770 phosphorylation was significantly increased in lymphocytes in first-episode psychosis compared to controls and decreased in patients treated with lithium compared to patients who did not receive lithium. Moreover, incubation with lithium but not olanzapine or valproic acid reduced SP4 phosphorylation in rat cultured cerebellar granule neurons. Conclusions The findings presented here indicate that SP4 S770 phosphorylation is increased in lymphocytes in first-episode psychosis which may be reduced by lithium treatment in patients. Moreover, our study shows lithium treatment prevents this phosphorylation in vitro in neurons. This pilot study suggests that S770 SP4 phosphorylation could be a peripheral biomarker of psychosis, and may be regulated by lithium treatment in first-episode psychosis.